Josie and the Pussycats - Bennett, Marguerite 1988-; Shannon, Kelsey; Morelli, Jack 1962- (Archie Comic Publications, 2017)
Join Josie, Valerie, and Melody in this retelling of their three-chord, power pop origin story. In this series kick-off, Josie's getting the band together to help achieve her dreams of musical stardom. But for the group to last, it needs a strong foundation of friendship and trust. Can the girls get going, or will Alexandra Cabot's plotting put a stop to the whole thing?
Keywords: Frau; Freundschaft; Musikgruppe; Comic